PERAN PERMAINAN TRADISIONAL SEBAGAI MEDIA BELAJAR PENDIDIKAN JASMANI DALAM MENGEMBANGKAN KETERAMPILAN SOSIAL SISWA SEKOLAH DASAR - Hutomo, Langgeng; Kurniawan, Wahyu Ragil (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
A Traditional games play an important role in Indonesian culture, not only as cultural heritage but also as an educational tool, particularly in physical education. This study examines how traditional games support the development of elementary students' social skills, focusing on teamwork, responsibility, hard work, and concern. A qualitative research method was used, involving interviews with students, physical education teachers, and school principals from eight elementary schools in Gugus Dewi Kunthi, Gunung Pati District, Semarang City. The findings indicate that traditional games such as Gobak Sodor, Engklek, Egrang, and Bentengan significantly enhance students' ability to collaborate, work diligently, and strengthen social relationships. However, several challenges hinder their implementation in schools, including time constraints in the curriculum, limited facilities, and a lack of teacher training. To maximize the benefits of traditional games, it is recommended that these activities be integrated into the curriculum, teacher training programs be enhanced, and supporting facilities be improved. Further research is needed to explore the cognitive and emotional impact of traditional games and develop a structured learning model that incorporates these activities.